Playing with Marked Cards, or Using Documents as a Tool for Historical Manipulation: the Case of Russian 'Archive Websites' - Zawistowski, Andrzej (Institute of European Network Remembrance and Solidarity, 2021)
Can genuine archival documents be used to manipulate our knowledge of the past? Of course, only three steps suffice: restrict historians' access to archives, select sources according to a desired premise and make sure your message reaches a wide audience, especially non-historians.